Implementasi Karakteristik Arsitektur sasak pada Bangunan Resort Studi Kasus: Bangunan Fasilitas Utama Aston Sunset Beach Resort, Gili Trawanganeach Resort di Gili Trawangan - kartika Tristanto; Harry Kurniawan (Journal of Architectural Design and Development (JAD), 2021)
Gili Trawangan is known as one of the tourists popular place to visit that is located in Lombok island where Sasak tribe origin from. Sasak tribes has distinctive buildings with certain characteristics. Aston Sunset Beach Resort is one of the resorts that provides and shows the nuances of traditional Sasak architecture, that the shape of the structure has caught the intention of the tourists who visit the resort. In order to find out how deep the Sasak architecture is applied to the resort building, it is necessary to conduct a research, with the aim of what parts are implemented and how the Sasak architecture implementation is in each room unit of building architecture at Aston Sunset Beach Resort. The method used in this study is a qualitative deductive method with a rationalistic paradigm, the data in this study were obtained based on literature studies and direct field observations, and the analysis was carried out by comparing the resort architecture data and the Sasak architectural study using predetermined parameters to find equations as well as the difference between the two, if a difference is found, it will be seen how far the difference is transformed or vice versa, which is significantly different from the character of Sasak architecture. The results of this research found that the implementation of Sasak architecture in several resort buildings is in various forms but does not necessarily apply to all of the constructions but the buildings still have the same characteristics